TNF-α inhibitor-induced alopecia in psoriatic disease patients: a pharmacovigilance study - Afroza, Halima (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.